An Assessment of the Breastfeeding Practices and Infant Feeding Pattern among Mothers in Mauritius - Ashmika Motee; Deerajen Ramasawmy; Prity Pugo-Gunsam; Rajesh Jeewon (Journal of Nutrition and Metabolism)
Proper breastfeeding practices are effective ways for reducing childhood morbidity and mortality. While many mothers understand the importance of breastfeeding, others are less knowledgeable on the benefits of breastfeeding and weaning. The aim in here is to assess breastfeeding pattern, infant formula feeding pattern, and weaning introduction in Mauritius and to investigate the factors that influence infant nutrition. 500 mothers were interviewed using a questionnaire which was designed to elicit information on infant feeding practices. Statistical analyses were done using SPSS (version 13.0), whereby chi-square tests were used to evaluate relationships between different selected variables. The prevalence of breastfeeding practice in Mauritius has risen from 72% in 1991 to 93.4% as found in this study, while only 17.9% breastfed their children exclusively for the first 6 months, and the mean duration of EBF (exclusive breastfeeding) is 2.10 months. Complementary feeding was more commonly initiated around 4–6 months (75.2%). Despite the fact that 60.6% of mothers initiate breastfeeding and 26.1% of mothers are found to breastfeed up to 2 years, the practice of EBF for the first 6 months is low (17.9%). Factors found to influence infant feeding practices are type of delivery, parity, alcohol consumption, occupation, education, and breast problems.